Implementation of Communicative Activities to Improve Twelfth Grade students’ English Speaking Skill at Santo Domingo de Guzman High School. - Ronquillo Chanalata, Leidys Fabiola (2016)
Having communicative competence is difficult for people who study English as a foreign language. This research was carried out because of the need students of twelfth grade of Santo Domingo de Guzmán High School have in successfully communicating orally with their teachers and classmates. The intention of this work was to design a guideline with activities centered on the task-based approach to help students improve their speaking skill. This report was devised using the qualitative method to analyse the level of communication of this group of students, what kind of activities they prefer and how some experts’ teaching techniques can help in the development of the proposal. It was found that the students need to enhance their vocabulary repertoire and their command of discourse markers when speaking. In addition, pronunciation deficiencies need to be tackled thorough communicative activities. The guideline proposed has been designed considering the results gathered.